2015
DOI: 10.3389/fpls.2014.00808
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental macronutrients and microbial fermentation products improve the uptake and transport of foliar applied zinc in sunflower (Helianthus annuus L.) plants. Studies utilizing micro X-ray florescence

Abstract: Enhancing nutrient uptake and the subsequent elemental transport from the sites of application to sites of utilization is of great importance to the science and practical field application of foliar fertilizers. The aim of this study was to investigate the mobility of various foliar applied zinc (Zn) formulations in sunflower (Helianthus annuus L.) and to evaluate the effects of the addition of an organic biostimulant on phloem loading and elemental mobility. This was achieved by application of foliar formulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 32 publications
2
27
0
Order By: Relevance
“…The results of the present study, in which the addition of SE or MI did not enhance the effects of the foliar Zn applications on grain concentration, are in part contradicting with the previous reports. For example, Tian et al [14] reported that foliar application of microbial incubates greatly enhanced the uptake and movement of foliar-applied Zn in sunflower. Several studies on horticultural crops have also shown that soil applications of seaweed extracts were able to improve uptake of Zn and other nutrients [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the present study, in which the addition of SE or MI did not enhance the effects of the foliar Zn applications on grain concentration, are in part contradicting with the previous reports. For example, Tian et al [14] reported that foliar application of microbial incubates greatly enhanced the uptake and movement of foliar-applied Zn in sunflower. Several studies on horticultural crops have also shown that soil applications of seaweed extracts were able to improve uptake of Zn and other nutrients [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies assessing the effect of these biostimulants have focused on promoting plant growth and productivity [13]; only a few studies have investigated the impact of foliar biostimulants on the uptake of micronutrients in plants, including Zn. For example, Tian et al [14] reported that foliar spray microbial inoculants increased the movement of leaf-applied Zn in sunflower. Koksal et al [15] showed that leaf-applied amino acid chelate in pear increased leaf Zn content.…”
mentioning
confidence: 99%
“…Tian et al [24] supplemented macronutrients and microbial fermentation products to improve the uptake and transport of foliarly applied zinc in sunflower (Helianthus annuus) by the micro X-ray florescence method when microbially derived organic biostimulant "GroZyme" was applied. Mobility of Zn from different preparations and phloem loading as the result of using an organic biostimulant were determined.…”
Section: Examples Of Innovative Bioproducts For Agriculturementioning
confidence: 99%
“…Evidence that biostimulants may enhance macro nutrient uptake has been reported previously (Calvo et al, 2014;Rose et al, 2014) and have been ascribed to an effect on sink activity or stimulation of nitrogen metabolism. Foliar application of a biostimulant derived from microbial fermentation of cereal grains (Tian et al, 2015) greatly enhanced the movement of foliar applied zinc in sunflower. Using high resolution elemental mapping techniques (µ-Xray Florescence) the movement of Zn to the phloem following application of a combination of biostimulant and zinc sulfate was elegantly demonstrated.…”
mentioning
confidence: 99%